The relationship of well-being, academic self-efficacy, and academic major satisfaction among part-time job students: A cross-sectional study - Phuoc-Thien NGUYEN; Hoai-Thang TO; Gia-Phuoc TRAN-THIEN; Thien-Ly DUONG-VO; Ky LUU; Ngoc-Han NGUYEN-THI; Vinh-Long TRAN-CHI (Journal of Health and Social Sciences)
Introduction: Part-time jobs are common among college students due to financial needs and personal development goals. While it offers benefits, its impact on student well-being, academic performance, and major satisfaction remains unclear. This research delves into the intricate links between part-time job, well-being, academic self-efficacy, and satisfaction with major selection, aiming to improve student support through a deeper understanding of these factors. Methods: This study analyzed 282 students with part-time employment after surveying and selecting them. For model analysis, PLS-SEM software was utilized, whereas SPSS software was applied for descriptive statistics and comparative analyses. Results: Of the total participants, 67.4% of students were females, while 32.6% of students were males. There were 22.7% freshmen, 37.2% sophomores, 28.0% juniors, and 12.1% seniors. This study indicated that academic major satisfaction is influenced by both mental health and academic self- efficacy; academic self-efficacy is influenced by mental health. Furthermore, academic self-efficacy acts as a mediator between mental health and academic major satisfaction. Moreover, parental income may be a factor influencing students' academic self-efficacy. Discussion: Our findings provide more evidence about the relationship between mental health, academic self-efficacy, and academic major satisfaction. To maximize students' academic self-efficacy and academic major satisfaction, schools must prioritize the mental wellness of their students.